Klimaschutz im Luftverkehr: Wie geht es weiter? Optionen zur zukünftigen Gestaltung des EU-Emissionshandels - Janina Scheelhaase; Wolfgang Grimme; Holger Pabst; Martin Jung; Jan Bechthold (Wirtschaftsdienst, 2016)
Der Luftverkehr trägt auf niedrigem Niveau, aber mit steigender Tendenz zur anthropogenen Klimaerwärmung bei. Seit 2012 unterliegen die CO2-Emissionen des internationalen Luftverkehrs in Europa dem EU-Emissionshandel - allerdings bis Ende 2016 in regional erheblich eingeschränktem Umfang. Ab 2020 soll eine 'marktbasierte Maßnahme' zur Begrenzung der CO2-Emissionen des internationalen Luftverkehrs auf globaler Ebene eingeführt werden. Um das zurzeit geltende System weiterzuentwickeln hat die EUKommission unterschiedliche Ausgestaltungsoptionen, die im Hinblick auf die damit verbundenen emissionsbezogenen und ökonomischen Effekte analysiert werden. – – The paper compares the impacts of alternative geographical scopes of flights integrated in the EU-Emission Trading System (EU-ETS) with regard to environmental and economic aspects. The core of the analysis is a geographical scope according to the 50:50 approach, in which half of the emissions of international aviation between European Economic Area (EEA) and third countries will be part of the EU-ETS. In total, seven options are analysed, which differ by the geographical scope and exceptions. Besides a pure 50:50 approach without any exceptions, we also discuss an option where emissions are capped at the border of a third country. Furthermore, another option assumes that all emissions in international airspace are being excluded from the EU-ETS. For comparison, the impacts of the Full Scope and Reduced Scope approaches are analysed and two options based on airspace, where emissions of flights to/from airports outside the EEA are fully regulated by EU-ETS, as long as they are emitted in EEA airspace or EEA and international airspace, respectively.
Keywords: Q58; H23; L93; 330